Science learning using the Flipped Blended Learning Model Based on Google Classroom's Learning Management System (LMS) - Zakaria, Zakaria; Ningsih, Sri Mutiara (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2024)
Natural Sciences (IPA) studies concepts about nature and natural phenomena that can be proven. However, not all students are able to understand the concept of science. To achieve science learning objectives requires innovative implementation of strategies, approaches, methods or learning media that are effective and efficient. This research aims to develop learning media based on the Google Classroom LMS, its feasibility and utilization with the flipped blended learning system. This development uses the ADDIE model (analysis, design, development, implementation, evaluation). The development of learning media based on the Google Classroom LMS consisting of learning material aspects (appropriateness of material, learning model, and language) obtained 97.27% (very good). The learning media aspect obtained a score of 87.00% (very good), while the student response results were 88.69% (very decent). This research shows that the flipped blended learning model based on the Google classroom learning management system (LMS) in science learning at MIN 7 Bone is very feasible to implement.